2022
DOI: 10.1002/smll.202203207
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Insights into the Triple Ionic and Electronic Conductivity of a Novel Nanocomposite Functional Material for Protonic Ceramic Fuel Cells

Abstract: Triple ionic and electronic conductivity (TIEC) in cathode materials for protonic ceramic fuel cells (PCFCs) is a desirable feature that enhances the spatial expansion of active reaction sites for electrochemical oxygen reduction reaction. The realization of optimal TIEC in single‐phase materials, however, is challenging. A facile route that facilitates the optimization of TIEC in PCFC cathodes is the strategic development of multiphase cathode materials. In this study, a cubic‐rhombohedral TIEC nanocomposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…This indicated that the porous CoMoO 4 + NiMoO 4 nanosheets had excellent electrical conductivity as an electrode material. 18 In the low-frequency region, the slope of the porous CoMoO 4 + NiMoO 4 nanosheets line was close to 901, which was much higher than that of the single substances CoMoO 4 and NiMoO 4 . This also indicated that the porous CoMoO 4 + NiMoO 4 nanosheets had a much smaller diffusion impedance.…”
Section: Resultsmentioning
confidence: 85%
“…This indicated that the porous CoMoO 4 + NiMoO 4 nanosheets had excellent electrical conductivity as an electrode material. 18 In the low-frequency region, the slope of the porous CoMoO 4 + NiMoO 4 nanosheets line was close to 901, which was much higher than that of the single substances CoMoO 4 and NiMoO 4 . This also indicated that the porous CoMoO 4 + NiMoO 4 nanosheets had a much smaller diffusion impedance.…”
Section: Resultsmentioning
confidence: 85%
“…140 Moreover, the composite material of Ba(CeCo) 0.4 (FeZr) 0.1 O 3Àd (BCCFZ) is composed of mixed ion and electron conducting phases of BaCo 1À(x+y+z) Ce x Fe y Zr z O 3Àd (M-BCCFZ) and dominant protonconducting phases of BaCe 1À(x+y+z) Co x Zr y Fe z O 3Àd (H-BCCZF). 141 The major Ce-rich phase of H-BCCFZ with a low protonation enthalpy of À30 AE 9 kJ mol À1 promotes the oxygen vacancy concentration and proton defect formation. 141 As shown in Fig.…”
Section: Reviewmentioning
confidence: 99%
“…141 The major Ce-rich phase of H-BCCFZ with a low protonation enthalpy of À30 AE 9 kJ mol À1 promotes the oxygen vacancy concentration and proton defect formation. 141 As shown in Fig. 7(f), the O 2À /e À conducting material of BSCF and the proton-conducting material of BZCYYb were synthesized by a one-pot self-assembly, in which the mixing of elements at the atomic level was calcined to form cation-exchanged two-phase composites that were homogeneously distributed and tightly attached on the nanoscale.…”
Section: Reviewmentioning
confidence: 99%
“…To gain further understanding of the reaction mechanism, the distribution of the relaxation time (DRT) technique was utilized to deconvolute the impedance response (Figure S6c). The DRT plot can be separated into three distinct frequency sections: high frequency (>10 4 Hz), intermediate frequency (10–10 4 Hz), and low frequency (10 –2 –10 Hz), which is consistent with the reports on PCFCs. , The high-, intermediate-, and low-frequency peaks correspond to the ion transfer across the electrolyte/electrode interface, surface exchange or ion transfer at the electrode bulk, and mass transfer in the electrode, respectively. Table S1 summarized the ASRs of tubular PCFCs fabricated by different methods at 650 °C.…”
mentioning
confidence: 99%